2012
DOI: 10.1007/s13197-012-0761-5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity and amino acid analysis of Caralluma adscendens (Roxb.) Haw var. fimbriata (wall.) Grav. & Mayur. aerial parts

Abstract: Caralluma adscendens (Roxb.) Haw var. fimbriata (wall.) Grav. & Mayur. is a traditional food consumed as vegetable or pickle in arid regions of India and eaten during famines. In Indian traditional medicine, the plant is used to treat diabetes, inflammation and etc. The aim of this study was to evaluate the antioxidant properties (DPPH, TEAC, TAA, FRAP, OH˙ and NO˙ radical scavenging activities) of the different extracts from aerial parts. The levels of total phenolics and flavonoids of the extracts were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…fimbriata. 32 Our results are in agreement with the reports of Chew et al (2009), 33 that methanol showed better recoveries and it is specifically effective in extracting polyphenols. Thus, solvents polarity plays a major role in extraction of the antioxidants.…”
Section: Discussionsupporting
confidence: 93%
“…fimbriata. 32 Our results are in agreement with the reports of Chew et al (2009), 33 that methanol showed better recoveries and it is specifically effective in extracting polyphenols. Thus, solvents polarity plays a major role in extraction of the antioxidants.…”
Section: Discussionsupporting
confidence: 93%
“…It is worth noting that C. europaea is rich in phenolic compounds; the total phenolic content of C. europaea hydroethanolic extract was 51.42 ± 0.003 mg GAE/g dry of extract. ese values were significantly higher than those of the methanolic and aqueous extract of C. adscendens, being 21.0 ± 0.59 and 18.8 ± 0.98 mg GAE/g dry extract, respectively [33].…”
Section: Discussionmentioning
confidence: 69%
“…Through this type of studies, certain extracts and their components can be recommended for use an additive in food preparations and nutraceuticals [39]. Al-Attabi et al [40] reported that the ethanol extract and ethyl acetate fraction from C. arabica have strong antioxidant activity.…”
Section: Total Phenol and Flavonoid Contentsmentioning
confidence: 99%